Clays and Clay Minerals, Vol. 60, No. 5, 535–552, 2012. - Ufer, Kristian; Kleeberg, Reinhard; Bergmann, Jorg; Dohrmann, Reiner (The Clay Minerals Society, 2012)
X-ray diffraction (XRD) of powdered materials is one of the most common methods used for structural characterization as well as for the quantification of mineral contents in mixtures. The application of the Rietveld method for that purpose requires structure models for each phase. The recursive calculation of structure factors was applied here to the Rietveld refinement of XRD powder patterns of illite-smectite (I-S) minerals. This approach allowed implementation of stacking disorder in structural models. Models for disordered stacking of cis-vacant and trans-vacant dioctahedral 2:1 layers as well as rotational disorder were combined with models for mixed layering of illitic and smectitic layers. The DIFFaX code was used to simulate non-basal (hk) reflections of illites with different degrees of disorder. Rietveld refinements of these simulated patterns were used to evaluate the application of this new approach. A model describing rotational disorder (n·120º and n·60º rotations) and mixed layering of cisvacant and trans-vacant dioctahedral layers was tested. Different starting parameters led to identical results within the ranges of standard deviations and confirmed the stability of the automatic refinement procedure. The influence on the refinement result of an incorrect choice of fixed parameters was demonstrated. The hk model was combined with models describing the basal reflections of disordered I-S and tested on measured data. A glauconitic mineral (Urkut, Hungary), an ordered I-S (ISCz-1, a special clay in the Source Clays Repository of The Clay Minerals Society), and a dioctahedral I-S (F4, Fu¨ze´rradva´ny, Hungary) were used as test substances. Parameters describing the mixed layering of illitic and smectitic layers were compared with the results from refinements of oriented mounts and showed good agreement. A pattern of a physical mixture of an I-S mineral and a turbostratically disordered smectite was analyzed in order to test the new approach for application in quantitative phase analysis. The quantitative Rietveld phase analysis results were found to be satisfactory.
Rietveld Refinement Of Disordered Illite-smectite Mixed-layer Structures By A Recursive Algorithm. Ii: Powder-pattern Refinement And Quantitative Phase Analysis
gsccm60508-ufe.pdf -- 1,823 KB
Keywords: Periodicals; Geology; BGMN; DIFFaX; Illite-smectite; Quantitative Phase Analysis; Rietveld Refinement; Stacking Faults